Boosting Energy Efficiency and Stability of Li–CO2 Batteries via Synergy between Ru Atom Clusters and Single‐Atom Ru–N4 sites in the Electrocatalyst Cathode. Issue 17 (25th March 2022) - Lin, Jiangfeng; Ding, Jingnan; Wang, Haozhi; Yang, Xinyi; Zheng, Xuerong; Huang, Zechuan; Song, Wanqing; Ding, Jia; Han, Xiaopeng; Hu, Wenbin
Abstract: The Li–CO2 battery is a novel strategy for CO2 capture and energy‐storage applications. However, the sluggish CO2 reduction and evolution reactions cause large overpotential and poor cycling performance. Herein, a new catalyst containing well‐defined ruthenium (Ru) atomic clusters (RuAC ) and single‐atom Ru–N4 (RuSA ) composite sites on carbon nanobox substrate (RuAC+SA @NCB) (NCB = nitrogen‐doped carbon nanobox) is fabricated by utilizing the different complexation effects between the Ru cation and the amine group (NH2 ) on carbon quantum dots or nitrogen moieties on NCB. Systematic experimental and theoretical investigations demonstrate the vital role of electronic synergy between RuAC and Ru–N4 in improving the electrocatalytic activity toward the CO2 evolution reaction (CO2 ER) and CO2 reduction reaction (CO2 RR). The electronic properties of the Ru–N4 sites are essentially modulated by the adjacent RuAC species, which optimizes the interactions with key reaction intermediates thereby reducing the energy barriers in the rate‐determining steps of the CO2 RR and CO2 ER. Remarkably, the RuAC+SA @NCB‐based cell displays unprecedented overpotentials as low as 1.65 and 1.86 V at ultrahigh rates of 1 and 2 A g −1, and twofold cycling lifespan than the baselines. The findings provide a novel strategy to construct catalysts with composite active sites comprising multiple atom assemblies for high‐performance metal–CO2 batteries. Abstract : A novel catalyst comprising ruthenium (Ru) atomic clusters and single‐atom sites (RuAC+SA ) is fabricated for boosting the energy efficiency and stability of Li–CO2 batteries. The improved CO2 reduction and evolution reaction kinetics stem from the unique electronic synergy between the adjacent Ru atomic cluster assemblies and Ru–N4 active sites.